Systematic Analysis of Differential H3K27me3 and H3K4me3 Deposition in Callus and Seedling Reveals the Epigenetic Regulatory Mechanisms Involved in Callus Formation in Rice - Zhao, Nannan; Zhang, Kang; Wang, Chunchao; Yan, Hengyu; Liu, Yue; Xu, Wenying; Su, Zhen (Frontiers in Genetics, 2020)
Plant growth and development process is indeed the cell meristematic process, and the cell fate transition process is accompanied by more obvious changes in epigenetic modification. Callus with cell pluripotency, has the ability to continue cell division, and is ideal for studying plant meristematic differentiation. By comparing the different epigenetic modifications between callus and seedling, the changes of chromatin state, the effects of different epigenetic modifications on the growth and development of plants can be revealed, and the key genes related to plant growth and development can be uncovered, and thus know the regulation of growth and development. In this study, we performed ChIP assays of different antibodies against rice seed-induced callus and seedlings grown for about 15 days, including H3K27me3 and H3K4me3. And the DHSs (DNase I hypersensitive sites) data for the corresponding tissues were downloaded from the public platform. In addition, we performed a significant analysis of the callus-decreased genes especially transcription factors, of H3K27me3, and found that the most of the transcription factors were related to growth and development including AP2-ERREBP, NAC, HB gene families, and others. And some of the reported genes related to meristemization such as OsWOX9, OsWOX11, OsPLT4, OsPLT5, OsSHR and the like were included therein. On the contrary, H3K4me3 could positively regulate the characteristics of callus through the higher deposition of H3K4me3 in callus than in seedling. We further performed transcriptome data analysis on 45 sets of Affymetrix GeneChip and finally obtained 1565 callus preferentially genes. At the same time, it was found that callus development and root development in rice had a common regulatory mechanism. For an in-depth study of these callus preferentially genes, we found that these genes associated with meristems require the removal of H3K27me3 and the deposition of H3K4me3 and DHS to be in a relatively active state in callus. Hopefully, our study about the epigenetic marks in callus and seedling can help to reveal the possible epigenetic mechanisms in callus formation and provide more resource for the study of cell division and differentiation.